Hubungan Antara Minat Baca Dengan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas IV SDN Kalegen 2 - Denis Agung Nugroho (Prosiding University Research Colloquium, 2021)
This study aims to determine the relationship between reading interest and studentlearning outcomes in Indonesian language subjects for fourth grade students at SDNKalegen 2 Bandongan, Magelang Regency. This research is a type of quantitativeresearch with a correlational research design. Research subjects were taken usingsaturated sampling technique with a total sample of 21 students. Data collectiontechniques were carried out using a reading interest questionnaire, interviews on readinginterest to students and documentation of student learning outcomes. The instrumentvalidation test of the questionnaire used the product moment formula while thereliability test used the Cronbach alpha formula with the help of the SPSS for WindowsV.26 program, the prerequisite test for normality and linearity, hypothesis testing usingthe non-parametric correlation Spearman rank analysis test technique because it doesnot meet the requirements to use parametric analysis test. The results showed that thecorrelation coefficient between the variable of reading interest and learning outcomes offourth grade Indonesian students had a value of 0.002 < 0.05 (the significance value wassmaller than the probability value). Meanwhile, the correlation figure is 0.645 in the highcategory and can be said to be positively related. So that there is a positive andsignificant relationship between reading interest and student learning outcomes inIndonesian class IV subjects. Thus the hypothesis is accepted.